Effects of monocular blur on clinical measurements of stereopsis and binocular contrast sensitivity - Mohd ‘Izzuddin Hairol,; Loshane Arusulem,; Wong, Jia Ying (Penerbit Universiti Kebangsaan Malaysia, 2017)
Visual conditions such as anisometropia, monovision and monocular undercorrection affect the combination of visual input from both eyes. This study investigated the effects of monocular blur, in binocularly normal participants, on stereoacuity and binocular contrast sensitivity. Fifteen young adults (age range between 19 and 23 years old) with normal visual acuity and binocular vision participated in this study. Stereopsis was measured using the TNO test with a series of positive spherical lenses placed before the dominant eye. The procedure was repeated using the Titmus Stereotest on five participants as a control experiment. Monocular and binocular contrast sensitivities were also measured using the Pelli-Robson Contrast Sensitivity Chart. Blur was induced monocularly with a series of positive spherical lenses placed before the dominant eye and binocular contrast sensitivity was re-measured. Stereopsis scores decreased significantly when monocular blur was imposed. Across blur levels, absolute stereopsis scores measured with TNO test were worse than those measured with Titmus stereotest (all p < 0.05). However, the ratio of scores obtained without blur and under monocular blur appeared to be similar for both tests. Stereopsis without blur was between 6.82× to 8× better than that obtained with the highest level of imposed monocular blur. Binocular contrast sensitivity score decreased significantly with increasing level of monocular blur (p < 0.01). Binocular contrast sensitivity score without blur was 1.62× better than that obtained under binocular viewing with highest level of imposed blur. Stereopsis tests are more sensitive than measurements of binocular contrast sensitivity as an indicator of interocular acuity discrepancies which could occur in anisometropic or monovision patients. However, the choice of stereopsis test is crucial, as the TNO test appears to be more sensitive to monocular blur than the Titmus stereostest.